_____ While Black: Millennial Race Play and the Post-Hip-Hop Generation. (August 2015) - Durham, Aisha
Millennials are defined by their savvy integration of digital communication technologies and by their seamless incorporation of difference that has been communicated through formal policies and multicultural representations. Although diverse media platforms and people appear commonplace within the millennial milieu, this generation still faces what Amiri Baraka describes as the changing same. The changing cultural landscape has not drastically shifted power relations nor has it dramatically transformed how we mediate blackness under postrace. This article will examine the real and imagined body of the slain Florida teen Trayvon Martin, particularly how his body has animated White racial humor and rage, and has activated a new civil rights movement informed by hip hop. The Florida-based author will situate Martin within the post-hip-hop generation and address state policies policing Martin and other Black youth. Vaudevillian blackface minstrelsy as a form of race play will provide a historical backdrop for a discussion about new media blackness, such as mobile gaming, and social media postcards of theme parties and race-planking called trayvoning. The author not only will address Martin as a specific site to project of collective racial longing but will also point to ways minoritized Y'ers are a part of the collective new dream defenders to challenge racial terror today.